Effect of number of implants, distal implant inclination, and angled abutment on stresses in fixed complete dentures: a nonlinear finite element analysis - Geremia,Tomás (2021)
Abstract Objectives: This nonlinear three-dimensional finite element analysis (FEA) study evaluated the effect of the number of implants, distal implant inclination, and use of angled abutments on stress magnitude and distribution in cortical bone (CB), abutment screw (AS), and prosthetic screw (PS) of implant-supported fixed complete dentures. Methods: Nonlinear 3D FEA models of mandibular fixed complete dentures were created with five, four, or three parallel straight implants (5S, 4S, 3S) and with tilted distal implants (5T, 4T, 3T). In addition, the 5T model was tested using angled abutments over the tilted distal implants to re-align the implant inclination. A 100-N axial load was applied over the first molar region (cantilever) to analyze the von Mises stresses in selected points (CB, AS, and PS). Results: The implant adjacent to the load showed the highest stresses in CB, AS, and PS. The model with three implants showed higher stresses than the ones with four and five implants. Peak stresses in the AS increased 40% from five to four implants and 100% from five to three implants. Tilting the distal implants increased stresses in CB. Peak stress in the PS increased 150% from 5S to 5T models and 100% from 4S to 4T models. Angled abutments generated lower stresses on CB and AS but higher stresses on PS. Conclusions: The results suggest that stresses in the cortical bone, abutment screw, and prosthetic screw increase when tilting the posterior implants and reducing the number of implants. The use of angled abutments decreased stresses at the bone-implant interface and in abutment screws but increased stresses on prosthetic screws.